Virtual Tide Gauge Observation of the 2006 Pangandaran Tsunami Using COMCOT Version 1.7 - Farikha Qurotun Uyun; Supriyadi; Sutikno; Mochamad Aryono Adhi; Hamzah Latief (Jurnal Fisika, 2024)
The 2006 Pangandaran tsunami was one of the most significant natural disasters in Indonesia, causing major damage to coastal infrastructure and extensive social impacts. This study aims to reconstruct the 2006 Pangandaran tsunami using topographic data from DEMNAS and bathymetry data from BATNAS by applying it to a fine grid size (nested model). The other purpose is to determine the validity of the model that has been made if verified using a comparison with the results of field surveys and calculations of Aida numbers. The research method used is by using topographic data from DEMNAS and bathymetry data from BATNAS as well as using earthquake mechanism data from Global CMT. Furthermore, it is simulated using COMCOT software version 1.7 as well as by creating a nested grid of 4 grids.  The obtained simulation results are then verified using field data and Aida numbers. The results of this study show that the earthquake with a magnitude of 7.7 Mw caused the movement of tectonic plates which resulted in a decrease and increase in sea level along the coast of Pangandaran. The simulation results have an Aida K value of 1.48 and an Aida